menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve the system by Substitution. 3x-y=-1 y= 2x-1
asked
Aug 2, 2021
85.0k
views
4
votes
Solve the system by Substitution.
3x-y=-1
y= 2x-1
Mathematics
middle-school
Maarten Derickx
asked
by
Maarten Derickx
5.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
5
votes
(-2,-5)...............
Executeinstaller
answered
Aug 4, 2021
by
Executeinstaller
5.6k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
1
vote
1.) Fill in y=2x-1 into the first equation
3x-(2x-1)=-1
3x-2x+1=-1
x+1=-1
x=-2
2.) Fill in x=-2 into y=2x-1
y=2(-2)-1
y=-4-1
y=-5
Your answer is (-2,-5) or x=-2 and y=-5
Tfwright
answered
Aug 8, 2021
by
Tfwright
5.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.3m
questions
6.8m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
how long Will it take for $7000 investment to grow to $7553 and the annual rate of 3.4% compounded quarterly assume that no withdrawals are made
I need to simplify this expression.
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org